2021
DOI: 10.3390/ijms22062946
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Postnatal High Linoleic Acid Diet Impacts Lipid Metabolism in Adult Rat Offspring in a Sex-Specific Manner

Abstract: Linoleic acid (LA), an n-6 polyunsaturated fatty acid (PUFA), is essential for fetal growth and development. We aimed to investigate the effect of maternal and postnatal high LA (HLA) diet on plasma FA composition, plasma and hepatic lipids and genes involved in lipid metabolism in the liver of adult offspring. Female rats were fed with low LA (LLA; 1.44% LA) or HLA (6.21% LA) diets for 10 weeks before pregnancy, and during gestation/lactation. Offspring were weaned at postnatal day 25 (PN25), fed either LLA o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 71 publications
1
17
1
Order By: Relevance
“…In rats, in the context of high-fat diet (HFD), high consumption of LA during pregnancy was reported to affect liver FA profiles of offspring in a similar manner, with increased ω6 PUFA and decreased MUFA ( Marchix et al, 2020a ). Surprisingly, however, and as previously observed in rabbits ( Tarrade et al, 2013 ) and rats ( Shrestha et al, 2021 ) fed with a high-fat diet rich in LA, FA concentrations in liver neutral lipids were similar among groups.…”
Section: Discussionsupporting
confidence: 82%
“…In rats, in the context of high-fat diet (HFD), high consumption of LA during pregnancy was reported to affect liver FA profiles of offspring in a similar manner, with increased ω6 PUFA and decreased MUFA ( Marchix et al, 2020a ). Surprisingly, however, and as previously observed in rabbits ( Tarrade et al, 2013 ) and rats ( Shrestha et al, 2021 ) fed with a high-fat diet rich in LA, FA concentrations in liver neutral lipids were similar among groups.…”
Section: Discussionsupporting
confidence: 82%
“…Pantothenate and CoA biosynthesis are strongly involved in the metabolism of the fatty acids, and a UPLC-MS-based urine nontargeted metabolic profiling implied that pantothenate and coenzyme A biosynthesis pathway alteration was the most prominent in diabetic kidney disease (a major prevalent chronic microvascular complication of type 2 diabetes) subjects [33]. Linoleic acid is competent in CO and has been widely proved to be linked with liver lipid accumulation [34,35]. Additionally, the current study indicated that linoleic acid metabolism is also involved in serum lipid levels.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we reported that maternal and postnatal diet high in LA alters metabolic parameters, mainly circulating leptin and cholesterol, in adult offspring in a sex-specific manner [ 15 ]. In this study, there is no alteration in measured metabolites among the dietary groups, so that maternal and postnatal LA had no effect on the distribution of metabolites in the adult offspring.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are limited data studying the effect of high LA diet during pregnancy on offspring health. Recently, we have demonstrated that high maternal LA affects offspring cardiac function [14] and metabolic parameters [15] in a rat model.…”
Section: Introductionmentioning
confidence: 99%